2008
DOI: 10.1103/physrevc.77.019904
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Dynamics ofK¯and multi-K¯nuclei [Phys. Rev. C 76, 055204 (2007)]

Abstract: We erroneously discussed in the published manuscript, between Eqs. (4) and (5) and in the beginning of Sec. III B, an 'I = 0 isospin configuration' for an even number κ = 0 ofK mesons. Bose Einstein statistics imposes I = κ/2 when all these mesons are placed in the lowest mean-field s-state, as considered in this work. Therefore, the dashed lines corresponding to the 'I = 0 configuration' in Fig. 8 are to be

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
104
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(115 citation statements)
references
References 0 publications
11
104
0
Order By: Relevance
“…In our calculations, we assumed the branching rate of B (Y N ) 2 = 0.2 in the K − pp decay processes. This value is often used in previous works for heavier targets [26,27,41,42] but it is experimentally unknown in the K − absorption on 3 He in flight. In terms of the K − absorption on 4 He at rest, the early data of the helium bubble chamber experiment [47] suggested that the ratio of the two-nucleon K − absorption to all the K − absorption processes amounts to 16 %, whereas its value depends on atomic orbits where K − is absorbed through atomic cascade processes [27,48].…”
Section: Discussionmentioning
confidence: 99%
“…In our calculations, we assumed the branching rate of B (Y N ) 2 = 0.2 in the K − pp decay processes. This value is often used in previous works for heavier targets [26,27,41,42] but it is experimentally unknown in the K − absorption on 3 He in flight. In terms of the K − absorption on 4 He at rest, the early data of the helium bubble chamber experiment [47] suggested that the ratio of the two-nucleon K − absorption to all the K − absorption processes amounts to 16 %, whereas its value depends on atomic orbits where K − is absorbed through atomic cascade processes [27,48].…”
Section: Discussionmentioning
confidence: 99%
“…We present only selected results of our dynamical calculations in Section 3. We refer the interested reader to our recent papers [25,26] for more detailed discussion. Conclusions are summarized in Section 4.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have studied multi-antikaonic nuclei (MKN), where several K − mesons are bound in the nucleus, based on a relativistic mean-field (RMF) model for baryon-baryon (B-B) interaction, combined with the effective chiral Lagrangian for kaon-baryon (K-B) and nonlinearK-K interactions [2]. (Similar results have been obtained for the MKN in [3], where kaonic part of the Lagrangian corresponds to that obtained by the lowest-order expansion with respect to the kaon field. )…”
Section: Introductionmentioning
confidence: 54%